Determinan Perilaku Gagal Bayar: Model Literasi Keuangan, Niat, dan Sifat Personal (Determinants of Default Behavior: Financial Literacy Model, Intention, and Personal Traits) - Annisa Afra Fortuna; Djohan Gunawan Hasan; Florentina Kurniasari (STIE Malangkucecwara, 2026)
Amidst the massive growth of online lending and the prevalence of loan default in Indonesia, this research tests an integrated behavioral model to identify its determinants, employing a quantitative PLS-SEM method on 213 online loan users in the Jabodetabek area. Key findings reveal that financial literacy consistently emerges as a significant protective factor. Conversely, the role of personal traits is more nuanced: self-control and materialism primarily influence risk perception rather than directly impacting default behavior. The study also confirms a perception-behavior gap, wherein risk awareness is insufficient to prevent default, while default intention, consistent with the Theory of Planned Behavior, proved to be the strongest proximal predictor of actual default. This study contributes by clarifying these complex behavioral roles and offers actionable implications for regulators and the fintech industry to design more effective risk mitigation strategies.